Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2000
DOI: 10.1002/j.1556-6676.2000.tb01932.x
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Social Connectedness in College Women and Men

Abstract: A sense of connectedness for men was hypothesized to be based on relationships that emphasize forms of social comparison, whereas a sense of connectedness for women was hypothesized to be based on relationships that emphasize forms of intimacy and physical proximity. The results from this study generally supported the hypotheses for both women and men. For women, relationships that emphasized reliable alliance and not guidance contributed to social connectedness. For men, relationships that emphasized reassura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
119
3

Year Published

2002
2002
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 164 publications
(137 citation statements)
references
References 35 publications
8
119
3
Order By: Relevance
“…In this regard, Lee and Robbins (1995) described social connectedness as the kind of relational scheme that signifies patterns found in interpersonal relationships. It was also explained to be a concept that is an enduring and ubiquitous self-sense in relationships to the world (Lee & Robbins, 2000) enabling individuals to perceive themselves as a part of the human race and to identify themselves with people they gravitate to (Lee & Robbins, 1995). In short, social connectedness refers to the way an individual relates with other individuals and his perception of himself in terms of networks and relationships.…”
Section: Social Connectednessmentioning
confidence: 99%
See 2 more Smart Citations
“…In this regard, Lee and Robbins (1995) described social connectedness as the kind of relational scheme that signifies patterns found in interpersonal relationships. It was also explained to be a concept that is an enduring and ubiquitous self-sense in relationships to the world (Lee & Robbins, 2000) enabling individuals to perceive themselves as a part of the human race and to identify themselves with people they gravitate to (Lee & Robbins, 1995). In short, social connectedness refers to the way an individual relates with other individuals and his perception of himself in terms of networks and relationships.…”
Section: Social Connectednessmentioning
confidence: 99%
“…Others related the construct to higher social competency and psychological health (e.g. Williams & Galliher, 2006), and increased self-esteem levels (Lee et al, 2001;Lee, Keough, & Sexton, 2002;Lee & Robbins, 2000). Still some other researchers like Pittman and Richmond (2007), Freeman et al (2007), and Mueller (2008) showed that school belonging has a crucial role in achievement motivation and psychological adjustment of college students and is related with the perceptions of the students of their faculty.…”
Section: The Effect Of Variables On Self-regulation Based On Studentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Research among college students by Lee and Robbins (2000) suggests that not the levels of connectedness differ between men and women, but the types of relationships and the kinds of social provision contributing to connectedness (see also Townsend and McWhirter 2005). For the men in their study, particularly relationships emphasizing social comparison played an important role, whereas for women relationships characterized by intimacy and reliable alliance were important.…”
mentioning
confidence: 99%
“…Lee and Robbins have identified social connectedness as an aspect of the self that reflects individual awareness of interpersonal closeness with the social world as a whole [28][29][30] . Campus connectedness is the characteristic of social connectedness relating to a student's connectedness and feelings of belonging with their peers in the context of a college environment 31 .…”
Section: Introductionmentioning
confidence: 99%